1976
DOI: 10.1007/bf00411429
|View full text |Cite
|
Sign up to set email alerts
|

Lysosomal enzymes in subretinal fluid

Abstract: Samples of subretinal fluid (SRF) from patients with primary rhegmatogeneous retinal detachment of various duration were studied using standard enzymologic techniques. The protein content in SRF increased with the duration of detachment. The activities of lysosomal enzymes in SRF, which were acid phosphatase, beta-glucuronidase, and cathepsin D, also increased with the duration of detachment. Especially cathepsin D, which was not detected in serum, was present in SRF. The activity of a nonlysosomal enzyme, i. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…For instance, CTSD was observed in Müller cells, ganglion cells and RPE cells of physiological retina [59,60], and the expression of CTSD correlated with age-related changes of the retina [61]. Finally, CTSD levels are high in SRF from patients with RRD [62]. Here, we demonstrate that CTSD was expressed significantly higher in SRF from patients with RRD than in NPDR, PDR, or PVR.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…For instance, CTSD was observed in Müller cells, ganglion cells and RPE cells of physiological retina [59,60], and the expression of CTSD correlated with age-related changes of the retina [61]. Finally, CTSD levels are high in SRF from patients with RRD [62]. Here, we demonstrate that CTSD was expressed significantly higher in SRF from patients with RRD than in NPDR, PDR, or PVR.…”
Section: Discussionmentioning
confidence: 56%
“…In the RRD and PVR samples, in comparison to the NPDR and PDR samples, there were significantly higher levels of PEDF, CLU, CTSD, and TTR detected. All of these proteins were reported to exist in RPE cells or glial cells that play an important role in pathogenesis of RRD and PVR [53][54][55][56][57][58][59][60][61][62][63][64], eloquently exhibiting the breakdown of retinal integrity and the flowing in of subretinal fluids into the vitreous samples.…”
Section: Discussionmentioning
confidence: 99%
“…The RPE is the main responsible for the phagocytosis of photoreceptor outer segments and by its consecutive lysosomal degradation [ 55 , 56 ]. Lysosomal proteins were previously found augmented in the vitreous and subretinal fluid, and their levels were related to RRD duration [ 57 , 58 ]. More recently, higher expression levels of cathepsin D were found in vitreous from patients with PVR [ 14 , 21 ], confirming our results.…”
Section: Discussionmentioning
confidence: 99%
“…So, it was suggested that the increase of lysosomal digestion is a later event in RD, contributing to the photoreceptor degeneration and inflammation [ 57 ]. Also, considering the role of vitreous liquefaction in RD onset [ 3 , 4 , 7 ], it has been suggested that lysosomal enzymes, mainly cathepsin D, may be involved in the degradation of glycosaminoglycans, and collagen molecules, of rod outer segments and RHO [ 55 , 58 , 59 ]. Finally, increased cathepsin A activity in the subretinal fluid was associated with retinal degradation in RD [ 59 ].…”
Section: Discussionmentioning
confidence: 99%